Pengembangan Media Pembelajaran dengan Pemanfaatan Aplikasi Wondershare Quizcreator - Isa, Yamanto; Sutiono, Edi; Rusdi, Mohamad Salman (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
The purpose of this research is to develop assessment media for learning using the Wondershare QuizCreator application in the Biology subject for Class XI Science at SMA Negeri 1 Cempaka OKU Timur. The research method used is the procedural engineering method employing survey-type data collection techniques. The research results show that media experts rated this product 85.3 in the "good" category. Design experts gave it a score of 82, also in the "good" category, while material experts rated it 82.1, again in the "good" category. Personal trials of the product by three respondents from the XI IPA class in the second semester yielded a score of 81.5 points, categorized as "good." A small group experiment with six respondents resulted in a score of 83.5, also categorized as "good." Subsequently, a large-scale test was conducted, and 26 respondents received a score of 81.7 points, categorized as "good." In conclusion, this media product for learning assessment is valid and suitable for use in the real world. Keywords: Biology, Evaluation, Media, Development